Dimensions fondant l’accompagnement de la personne souffrante en counseling et en psychothérapie : Résultats d’une recherche coopérative - Ratté, Jimmy; Caouette, Louise; Dubois, Alain; Lesage, Gino (Canadian Journal of Counselling and Psychotherapy, 2008)
This exploratory study uses a non-conventional method in qualitative research on the fundamental dimensions of counselling and psychotherapy to explore the phenomenon of the accompanying relationship based on the experience of one of the protagonists, the psychotherapist. The article does not aim to demonstrate the effectiveness of an approach, but rather to identify the dimensions that essentially allow a suffering person to become aware of his or her existential burden and experience growth in self and in various areas of life.